Atg17/FIP200 localizes to perilysosomal Ref(2)P aggregates and promotes autophagy by activation of Atg1 in Drosophila. - Nagy, P.; Kárpáti, M.; Varga, A.; Pircs, K.; Venkei, Z.; Takáts, S.; Varga, K.; Erdi, B.; Heged?s, K.; Juhász, G. (Autophagy, 2014)
Phagophore-derived autophagosomes deliver cytoplasmic material to lysosomes for degradation and reuse. Autophagy mediated by the incompletely characterized actions of Atg proteins is involved in numerous physiological and pathological settings including stress resistance, immunity, aging, cancer, and neurodegenerative diseases. Here we characterized Atg17/FIP200, the Drosophila ortholog of mammalian RB1CC1/FIP200, a proposed functional equivalent of yeast Atg17. Atg17 disruption inhibits basal, starvation-induced and developmental autophagy, and interferes with the programmed elimination of larval salivary glands and midgut during metamorphosis. Upon starvation, Atg17-positive structures appear at aggregates of the selective cargo Ref(2)P/p62 near lysosomes. This location may be similar to the perivacuolar PAS (phagophore assembly site) described in yeast. Drosophila Atg17 is a member of the Atg1 kinase complex as in mammals, and we showed that it binds to the other subunits including Atg1, Atg13, and Atg101 (C12orf44 in humans, 9430023L20Rik in mice and RGD1359310 in rats). Atg17 is required for the kinase activity of endogenous Atg1 in vivo, as loss of Atg17 prevents the Atg1-dependent shift of endogenous Atg13 to hyperphosphorylated forms, and also blocks punctate Atg1 localization during starvation. Finally, we found that Atg1 overexpression induces autophagy and reduces cell size in Atg17-null mutant fat body cells, and that overexpression of Atg17 promotes endogenous Atg13 phosphorylation and enhances autophagy in an Atg1-dependent manner in the fat body. We propose a model according to which the relative activity of Atg1, estimated by the ratio of hyper- to hypophosphorylated Atg13, contributes to setting low (basal) vs. high (starvation-induced) autophagy levels in Drosophila.